On Frobenius groups with noninvariant factor SL 2(3) - Kozulin, S. N.; Senashov, V. I.; Shunkov, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We obtain a criterion for the unsimplicity of an infinite group containing the infinite class of the Frobenius groups L_g = a, g^-1 a g with complement SL_2 ( 3 ).